Zap. - Schoenbach, K.H (IEEE spectrum)
Bioelectrics is an emerging field of research that combines the disciplines of high voltage engineering and cell biology to gain a better understanding of the effects of powerful, ultrashort voltage pulses on living tissue. Bioelectrics depends on advanced pulsed power technology, which is the ability to switch on and off thousands of amperes of current and just as many volts in mere nanoseconds. The most promising and practical result so far has been the recent discovery that certain pulsed electric fields can wipe out skin tumors in mice. Although many years will pass before it will even be worth testing on humans, bioelectrics offers a totally new therapeutic avenue - one that could lead to a therapy free of the debilitating side effects of chemotherapy drugs and tissue damage of radiation